2012
DOI: 10.1002/ejoc.201200457
|View full text |Cite
|
Sign up to set email alerts
|

CHBr3/TiCl4/Mg as an Unusual Nucleophilic CBr2 Carbenoid: Effective and Chemoselective Dibromomethylenation of Aldehydes and Ketones

Abstract: We report that instead of using CBr4, CHBr3 can serve as a highly nucleophilic dibromomethylene carbenoid in chemoselective carbonyl dibromomethylenation. Successful application of the dibromomethylenation to various carbonyl compounds such as enolizable and sterically hindered ketones by using the CHBr3/Mg/TiCl4 system highlights the weakly basic nature, extraordinary reactivity, and synthetic versatility of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, we found out that triisopropyl phosphite is not, in fact, easily removed after the reaction. Although on a small scale chromatography could be used, the harsher conditions required for triisopropyl phosphite hydrolysis (conc HCl–AcOH, reflux overnight) during larger-scale applications were not compatible with our compounds, leading to decomposition. We tested a variety of alkyl phosphites in this reaction (Table ) and were fortunate to discover that trimethyl phosphite/CBr 4 in toluene, when used at the ratio of ca.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found out that triisopropyl phosphite is not, in fact, easily removed after the reaction. Although on a small scale chromatography could be used, the harsher conditions required for triisopropyl phosphite hydrolysis (conc HCl–AcOH, reflux overnight) during larger-scale applications were not compatible with our compounds, leading to decomposition. We tested a variety of alkyl phosphites in this reaction (Table ) and were fortunate to discover that trimethyl phosphite/CBr 4 in toluene, when used at the ratio of ca.…”
Section: Resultsmentioning
confidence: 99%
“… and subsequently with some variation by Corey and Fuchs . More recently, a metal‐induced modification with CHBr 3 /TiCl 4 /Mg was used for such a transformation . It was also shown that a perchlorate phosphine salt as well as triisopropyl phosphite can replace PPh 3 in generating gem ‐dihaloolefins .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the probes started with the commercial benzophenone 3 that was protected with a TBDMS group and then converted to dibromide 5 by reaction with bromoform, magnesium, and TiCl 4 in 65% yield. 31 It should be noted that the more traditional Corey−Fuchs approach provided only traces of product 5 after refluxing for 24 h in toluene. 32 Subsequently, palladium-catalyzed borylation afforded intermediate 6 that was used for Suzuki coupling with enantiomeric bromides.…”
mentioning
confidence: 99%
“…In the case of a probe with racemic sulfoxides, the presence of a meso form would allow only partial reduction that would complicate the design and the interpretation of the data. The synthesis of the probes started with the commercial benzophenone 3 that was protected with a TBDMS group and then converted to dibromide 5 by reaction with bromoform, magnesium, and TiCl 4 in 65% yield . It should be noted that the more traditional Corey–Fuchs approach provided only traces of product 5 after refluxing for 24 h in toluene .…”
mentioning
confidence: 99%